Congenital factor XIII deficiency in Pakistan: characterization of seven families and identification of four novel mutations. (16th December 2013) - Borhany, M.; Handrkova, H.; Cairo, A.; Schroeder, V.; Fatima, N.; Naz, A.; Amanat, S.; Shamsi, T.; Peyvandi, F.; Kohler, H. P.
Summary Deficiency of coagulation factor XIII (FXIII) belongs to the rare bleeding disorders and its incidence is higher in populations with consanguineous marriages. The aims of this study were to characterize patients and relatives from seven families with suspected FXIII deficiency from Pakistan and to identify the underlying mutations. As a first indicator of FXIII deficiency, a 5M urea clot solubility test was used. Plasma FXIII A‐ and B‐subunit antigen levels were determined by ELISA. FXIII activity was measured with an incorporation assay. Sequencing of all exons and intron/exon boundaries of F13A was performed, and a novel splice site defect was confirmed by RT‐PCR analysis. Genetic analysis revealed six different mutations in the F13A gene. Two splice site mutations were detected, a novel c.1460+1G>A mutation in the first nucleotide of intron 11 and a previously reported c.2045G>A mutation in the last nucleotide of exon 14. Neither of them was expressed at protein level. A novel nonsense mutation in exon 4, c.567T>A, p.Cys188X, was identified, leading in homozygous form to severe FXIII deficiency. Two novel missense mutations were found in exons 8 and 9, c.1040C>A, p.Ala346Asp and c.1126T>C, p.Trp375Arg, and a previously reported missense mutation in exon 10, c.1241C>T, p.Ser413Leu. All patients homozygous for these missense mutations presented with severe FXIII deficiency. We have analysed a cohort of 27 individuals and reported four novel mutations leading to congenital FXIII deficiency.